LEGAL PROTECTION SYSTEM FOR EQUITABLE REMUNERATION - Abduh, Rachmad (Proceeding International Seminar of Islamic Studies, 2023)
Employment is all matters relating to the workforce at the time before, during and after the work period. The phenomenon experienced by workers is that the wages they receive are not commensurate with the cost of living, the high cost of living makes workers far from prosperous. In addition to meeting basic needs, such as clothing, food and boards, workers must also bear the cost of education for their children and must also set aside a portion of their wages to be used when workers are unable to work anymore. According to Idan Hanifah,